Dampak pembelajaran daring terhadap hasil belajar matematika siswa kelas V SD Negeri Muhammadiyah 01 Medan tahun 2020/2021 - Sinurat, Swandi Wiranata (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
This study seeks to see whether there is an impact of online learning on student mathematics learning outcomes in class V SD Negeri Muhammadiyah 01 Medan. Specifically, this study aims to determine the impact of online learning on student mathematics learning outcomes in class V SD Negeri Muhammadiyah 01 Medan. The hypothesis of this research is that there is an impact of online learning on mathematics learning outcomes and the decline in mathematics learning outcomes of students in class V SD Negeri Muhammadiyah 01 Medan. The approach used in this research is a quantitative approach with a quasi-experimental research type. The population in this study were the fifth grade students of SD Negeri Muhammadiyah 01 Medan which consisted of 25 students. Sampling using purposive sampling technique with a total sample of 25 students sonsisting of 10 male students and 15 female students. The data collection method used was test administration. The data analysis technique used is statistical analysis two-way test and one-way test (left) at the level of 5% or . Based on the discussion of the results of the study, it was found that there was an impact of online learning on mathematics learning outcomes, namely the decline in mathematics learning outcomes or the value did not reach the KKM of mathematics for grade V students of SD Negeri Muhammadiyah 01 Medan on determine the area of the trapezoid and kite. The ability of students to complete the test questions that was successful was only 36%.